Study of Distribution of Tumours in Pharyngeal, Laryngeal, Maxillary and Nasal Cavity Region - Azad, Dr. K. L.; Bhargava, Dr. Om Prakash (International Journal of Innovative Research in Medical Science, 2018)
Background: In India although infections and malnutrition are the factors contributing to morbidity and mortality, but now a days neoplastic diseases are coming into greater focus because of the preventive measure and better treatment being taken for the infections Objective was to study the distribution of tumours in “Pharyngeal, Laryngeal, Maxillary and Nasal Cavity Region” in patients attending medical college Hospital Jabalpur. Methods: The present study comprises of 379 patients who attended the outpatient department or were admitted in the wards of associated hospital of N.S.C.B. Medical College, Jabalpur during the period from July 2003 to July 2005 with the presenting complaint of Tumour. The study was carried out for two years. Permission from Institutional Ethics Committee was obtained. From each and every patient included in the study, initially informed individual consent was taken. Results: Incidence of total malignant tumours of salivary gland in respect to total malignant tumours of head and neck was 1.5 percent. Age and Site Distribution of Pharyngeal, Laryngeal, Maxillary sinus and Nasal cavity tumours, maximum number of tumours fall into the (35-74) age group, while only 2 cases were in the paediatric age groups which were in nasal cavity. Sex distribution of Pharyngeal, Laryngeal, Maxillary sinus and Nasal cavity tumours shows that male to female ratio was very high in all the sites except maxillary sinus and nasal cavity tumours. Conclusion: Incidence, patterns and trends of head and neck tumours were analyzed in all age group patients. Our study includes 379 cases diagnosed in NSCB Medical College and Hospital, Jabalpur during July 2003 to July 2005. Incidence of total malignant tumours of salivary gland in respect to total malignant tumours of head and neck was 1.5 percent. Incidence of benign tumours in respect to various benign tumours of head and neck was 16.8 percent.